Argentina : Selected Issues. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses whether there is a more efficient way of taxing labor in Argentina that has a minimal cost in terms of foregone revenues. Social security contributions for dependent workers are generally high in Argentina, despite the plethora of different regimes and exceptions. A reform of labor taxation in Argentina would need to address these inefficiencies. Reducing the tax wedge would stimulate employment and formalization, especially if targeted to low-paid workers, as there is evidence that it's their employment that mostly responds to tax incentives. Argentina's tax and transfer system appears to be less progressive than the estimated optimal one. The simulations suggest that the proposed changes would have a positive impact on economic activity and formality, with a minor cost in terms of foregone revenues. Greater labor supply and wages in the formal sector push up revenue from labor taxation, compensating part of the direct cost of the reform.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet